Syntactic Complexity in RA Writing of Chinese EFL Learners: A Corpus-Based Study of RA Abstracts - Li, Xinxin (Research and Advances in Education, 2025)
As a reliable measurement of language development, second language (L2) proficiency and writing quality, syntactic complexity has received considerable attention in research about L2 acquisition and English academic writing. However, few comparative studies have been conducted on the RAs (research articles) of Chinese EFL learners at undergraduate, graduate and PhD level using fine-grained indicators. Therefore, this study aims to examine the differences in syntactic complexity of academic output of Chinese across-proficiency L2 learners, as well as indicators with great predictive power towards English academic writing quality. Based on a self-constructed corpus, this study analyzed the abstract sections of 90 theses of Chinese EFL learners at undergraduate, graduate and PhD level in the field of Applied Linguistics. Using TAASSC, these samples were analyzed using 14 holistic metrics and 163 fine-grained metrics covering multiple dimensions of syntactic complexity. Significant differences in syntactic complexity among these cross-proficiency Chinese EFL learners in three groups were found. At the global level, syntactic complexity differs in the length of production units, the use of complex nouns and verb phrases per T-unit. At the fine-grained clausal level, syntactic complexity differences are reflected in the undefined subordination and auxiliary verbs per clause. At the fine-grained phrase level, syntactic complexity features differ in the subordinate components and six specific phrase subordination types. In addition, metrics that can effectively distinguish English L2 academic writing quality are revealed, namely, dependent clauses per clause, dependents per nominal subject (standard deviation) and adjectival modifiers per direct object (no pronouns). Results of this study can not only enrich the current study in terms of research subjects and indicators, but can also provide pedagogical implications for English for Research Publication Purposes (ERPP) teaching in China.